Digitalisasi Eco-Pesantren: Podcastpreneurship sebagai Strategi Pemberdayaan Ekonomi dan Kepemimpinan Santri Pesantren Tahfiz Assyifa Al-Islami Desa Waru Jaya, Bogor - Ahmad Maulidizen; Hayati, Setiyo; Nugraha, Risman; Setiawan, Agung; Asis, Alfian Airlangga; As Shofy, Muhammad Ulil Abshor; Azzami, Muhammad Naufal (Jurnal Pengabdian Masyarakat, 2025)
This Community Service Program (PKM) was conducted at Pesantren Tahfiz Assyifa Al-Islami, Waru Jaya Village, Bogor, aiming to empower students through the digitalization of pesantren economy based on podcastpreneurship. The program was motivated by the limited capacity of students in managing creative economic potential and developing digital leadership within Islamic boarding schools. Through a series of training and mentoring activities, the PKM team introduced the concept of a digital eco-pesantren, integrating Islamic entrepreneurship values, podcast technology, and digital da’wah communication strategies. The activities included podcastpreneurship workshops, creative content production, and the establishment of a mini digital studio as a medium for economic empowerment and leadership development. The results revealed significant improvements in students’ digital communication skills, entrepreneurial motivation, and ability to produce technology-based da’wah content. This program serves as an integrative model linking pesantren education, Islamic economics, and sustainable digital transformation toward Muslim community empowerment.